Pelatihan Alat Musik Drum Band Untuk Menambah Kreatifitas dan Disiplin Pada Siswa SDN Pragaan Laok I Kecamatan Pragaan Kabupaten Sumenep - Hanifatur Rizqi; Eko Adi Sumitro (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Marching Band or Drum Band refers to a group of people who play one or several songs using a number of combinations of musical instruments (wind, percussion, and a number of pit instruments) together. SDN Pragaan Laok I Marching Band Team was formed based on the Decree of the Principal of SDN Pragaan Laok I on July 22 2023 regarding the inauguration of extra-curricular members of the Marching Band.The partner's problem is the lack of extra-curricular deumband trainers, which makes the students (Gita Eka Praga Drumband Players) get less motivated to practice drumband musical instruments and causes a lack of discipline in following and undergoing extra-curricular drumband training. Based on the partner problems, researchers or providers create several questions or questionnaires which related to the causes of lack of discipline among Pragaan Laok I Elementary School students in participating of extracurricular drum band training and do the training in an ccording to the practice schedule so that they can provide solutions in increasing creativity and discipline for students in art world..